The Influence Of Liquidity, Profitability, Leverage, And Firm Size On Stock Returns With Environmental Performance As A Moderating Variable In Energy Sector Companies - Alansjah, Beni; Syarif, Andam Dewi (International Journal Labs, 2025)
This study aims to analyze the influence of liquidity, profitability, leverage, and company size on stock returns, with environmental performance as a moderation variable in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The method used is a quantitative approach with a panel data regression technique, using secondary data in the form of annual financial reports and PROPER scores from the Ministry of Environment and Forestry as indicators of environmental performance. The results of the study show that partially, only leverage has a significant negative effect on stock returns. Meanwhile, liquidity, profitability, and firm size did not show a significant influence. The environmental performance variable also does not have a significant effect on stock returns. However, the interaction between leverage and environmental performance has a significant positive effect, indicating that good environmental practices can moderate the negative impact of leverage on stock returns. These findings underscore the importance of integrating sustainability aspects into the company's financial strategy to increase investor confidence, especially in the energy sector which has high environmental risks.